2019
DOI: 10.1093/erae/jbz028
|View full text |Cite
|
Sign up to set email alerts
|

Growing condition variations and grain prices in Niger and Nigeria

Abstract: In this paper, we describe how both the existing degree of price correspondence and tradability are important factors explaining why and the extent to which grain price relationships adjust due to growing condition variations. For a set of maize and millet markets in Niger and Nigeria with different agro-ecological characteristics and strengths of price relationships, we use normalised difference vegetation index (NDVI) data to identify years with weather-related production shocks. We then measure the degree t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 18 publications
2
9
0
Order By: Relevance
“…These findings that supply‐related factors in importing regions influence the degree to which prices in trade partner countries move together is consistent with results from studies that included trade‐related variables in price transmission models, such as those by Barrett and Li (2002), Stephens et al (2012), and Arnade and Hoffman (2019). This paper also shows that that NDVI is a useful, timely, and accessible measure of growing condition variations that can be encompassed as a proxy for supply into price formation and transmission models, as was also demonstrated by Brown and Kshirsagar (2015), Baffes et al (2019), and Hatzenbuehler et al (2020).…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…These findings that supply‐related factors in importing regions influence the degree to which prices in trade partner countries move together is consistent with results from studies that included trade‐related variables in price transmission models, such as those by Barrett and Li (2002), Stephens et al (2012), and Arnade and Hoffman (2019). This paper also shows that that NDVI is a useful, timely, and accessible measure of growing condition variations that can be encompassed as a proxy for supply into price formation and transmission models, as was also demonstrated by Brown and Kshirsagar (2015), Baffes et al (2019), and Hatzenbuehler et al (2020).…”
Section: Discussionsupporting
confidence: 67%
“…The NDVI is a measure of vegetation “greenness” that is global in scope and able to measure light reflectance from nearly every parcel of land on earth. It has been used as a proxy for agricultural production by recent studies such as Brown and Kshirsagar (2015), Baffes et al (2019), and Hatzenbuehler et al (2020). NDVI data can be downloaded at 16‐day or monthly intervals from February 2000 to the current period.…”
Section: Literature Review: Price Transmission With Growing Conditions Variation and Sparse Market Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…The extreme sensitivity of agricultural commodity prices to weather anomalies and fluctuations is well known. A substantive strand of empirical research has investigated this linkage and has shown that the causal chain can act either indirectly via the role played by crop yields and production volumes or through consumption choices (D'Agostino & Schlenker, 2016; Dercon, 2004; Hirvonen, 2016; Parker & Meretsky, 2004; Schlenker & Roberts, 2006; Schlenker & Roberts, 2009) or directly through spatial price transmission induced by factors such as market integration, networking, and trade arbitrage (Baffes et al, 2017; Brown & Kshirsagar, 2015; Gilbert et al, 2017; Haile et al, 2015; Hatzenbuehler et al, 2019; Mawejje, 2016; Minot, 2010; Stephens et al, 2012). The disruptive consequences of weather extremes on international prices (Algieri, 2014; Chatzopoulos et al, 2019; Headey & Fan, 2008; Piesse & Thirtle, 2009) and regional conflicts (Klomp & Bulte, 2013; Maystadt & Ecker, 2014) have also been studied extensively.…”
Section: Literature On Weather and Food Pricesmentioning
confidence: 99%
“…Such literature pointed out the presence of different price elasticities as a function of the specific crop-country combination, the sensitivity of the local food system to domestic production, and the degree of openness to international markets. Much less investigated, yet, is the crucial role of information flows in influencing spatial price adjustment across seasons, with the only exceptions of Stephens et al (2012) and Hatzenbuehler et al (2019). Furthermore, this body of empirical research on the weather-price relationship typically explores post-harvest price dynamics rather than pre-harvest ones.…”
Section: Literature On Weather and Food Pricesmentioning
confidence: 99%